Human immunodeficiency virus associated thrombotic thrombocytopenic purpura--favourable outcome with plasma exchange and prompt initiation of highly active antiretroviral therapy. - Hart, Daniel; Sayer, Ruth; Miller, Robert; Edwards, Simon; Kelly, Anne; Baglin, Trevor; Hunt, Beverley; Benjamin, Sylvia; Patel, Raj; Machin, Samuel; Scully, Marie (British journal of haematology, 2011)
Thrombotic thrombocytopenic purpura (TTP) is an acute prothrombotic disorder. Human immunodeficiency virus (HIV) is an identified precipitant. This study reviewed 30 episodes of HIV-associated TTP in 24 patients from the South-East England Apheresis units, over the last 10 years. All patients were heterosexual Black Africans. First presentation of TTP revealed a new diagnosis of HIV in eight patients. TTP relapse occurred on six occasions (in four patients) as a result of non-adherence to highly active antiretroviral therapy (HAART). Prompt initiation/re-initiation of HAART in parallel with plasma exchange (PEX)±steroid led to prompt remission. Adjunct immunomodulatory agents (e.g. Rituximab) were required in 10% of cases. Once-daily HAART regimens are recommended, being compatible with PEX requirement, maximizing drug exposure between PEX. High viral loads (>500,000 copies/ml) require more PEX to remission. ADAMTS13 activity was reduced (<5%) as detected by collagen-binding assay and anti-ADAMTS13 immunoglobulin G antibodies were raised in 80%. Continued HAART-adherence ensured a durable TTP remission with associated viral control resulting in no evidence of relapse. PEX and HAART are associated with replenishment of ADAMTS13 and viral suppression. More PEX is required in cases with higher viral loads. Continued HAART maintains remission. In a small proportion of cases, further immunomodulatory therapy may be required.
Keywords: Acute Disease; Adolescent; Adult; Antiretroviral Therapy, Highly Active; Child; Child, Preschool; Female; HIV Infections; Humans; Infant; Male; Medication Adherence; Middle Aged; Plasma Exchange; Purpura, Thrombotic Thrombocytopenic; Recurrence; Retrospective Studies; Treatment Outcome; Viral Load; Young Adult